Natural pathology of the captive chimpanzee (Pan troglodytes): A 35‐year review. Issue 5 (23rd May 2017) - Kumar, Shyamesh; Laurence, Hannah; Owston, Michael A.; Sharp, R. Mark; Williams, Priscilla; Lanford, Robert E.; Hubbard, Gene B.; Dick, Edward J.
Abstract: We present the spontaneous pathological lesions identified as a result of necropsy or biopsy for 245 chimpanzees ( Pan troglodytes ) over a 35‐year period. A review of the pathology database was performed for all diagnoses on chimpanzees from 1980 to 2014. All morphologic diagnoses, associated system, organ, etiology, and demographic information were reviewed and analyzed. Cardiomyopathy was the most frequent lesion observed followed by hemosiderosis, hyperplasia, nematodiasis, edema, and hemorrhage. The most frequently affected systems were the gastrointestinal, cardiovascular, urogenital, respiratory, and lymphatic/hematopoietic systems. The most common etiology was undetermined, followed by degenerative, physiologic, neoplastic, parasitic, and bacterial. Perinatal and infant animals were mostly affected by physiologic etiologies and chimpanzee‐induced trauma. Bacterial and physiologic etiologies were more common in juvenile animals. Degenerative and physiologic (and neoplastic in geriatric animals) etiologies predominated in adult, middle aged, and geriatric chimpanzees.